Between IT and societal shift: Preconditions of open strategizing - Kozarkiewicz, Alina (Od IT do przemian społecznych: uwarunkowania otwartych strategii, 2018)
The main aim of this paper is to indicate and analyse the primary conditions needed to implement the concept of open strategizing into the practice of an organization, as well as to make it successful. The structure of the paper comprises two main parts: a brief introduction to the most important issues of open strategy is followed by the results of own research. Two major approaches towards the notion of open strategy are delineated: the first is more oriented towards strategy content and based on the idea of comprising collaborative initiatives into a firm’s strategic plans, and the second refers to strategic management process, based on including external and internal actors (stakeholders) into strategizing processes. Within own research based on literature review and the re-reading of case materials, four categories of preconditions of open strategizing are revealed. These categories, described and illustrated by examples, comprise: level and quality of social IT implementation, open culture and leadership, capabilities and competences, as well as the perceived expected benefits from inclusion and transparency.
Management Sciences = Nauki o Zarządzaniu, 2018, vol. 23, no. 4; s. 3-8
Keywords: open innovations; open strategy; transparency; inclusion; social media; otwarte innowacje; otwarta strategia; transparentność; włączanie; media społecznościowe